2015
DOI: 10.1002/arp.1510
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Research Strategy for the Evaluation of Settlement Pits: 3D Electrical Resistivity Tomography, Magnetic Prospection and Soil Chemistry

Abstract: Irrespective of the region and time period, settlement pits are common features at archaeological sites. Variations in shape, size and fill reflect great diversity in terms of primary and secondary functions. Careful analysis of these aspects and a pit's refilling history yield key information for the reconstruction of economic, social and chronological aspects of settlement history. At present, it is unusual for a settlement site to undergo complete excavation; in most cases, only small areas within a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Most geophysical surveys now employ multiple methods under the premise that each might reveal different aspects of the subsurface (Clay, ; Forte & Pipan, ; Nowaczinski et al, ). Indeed, Weymouth () long ago emphasized that many geophysical properties represent independent or nearly independent dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most geophysical surveys now employ multiple methods under the premise that each might reveal different aspects of the subsurface (Clay, ; Forte & Pipan, ; Nowaczinski et al, ). Indeed, Weymouth () long ago emphasized that many geophysical properties represent independent or nearly independent dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that high eigenvalues associated with first principal components that exhibit loadings in the same direction point to zones of mutually high parallel correlation. KEYWORDS data integration, geophysical correlation, Great War, local correlation, local PCA, multi-method surveys 1 | INTRODUCTION Most geophysical surveys now employ multiple methods under the premise that each might reveal different aspects of the subsurface (Clay, 2001;Forte & Pipan, 2008;Nowaczinski et al, 2015). Indeed, Weymouth (1986) long ago emphasized that many geophysical properties represent independent or nearly independent dimensions.…”
mentioning
confidence: 99%
“…The hearth in Trench 2 was much larger, about 1.8-2 m in diameter and comprised a low pise kerb with a plaster render with a heat well at the top, also against the wall. Based on the success for detecting hearths on other Bronze Age sites, it was anticipated that the gradiometer would pick up the burning associated within them (Nowaczinski et al 2015;Papadopoulos et al 2006;Urban et al 2014a, b). Although there is a moderate magnetic change with the hearth in Trench 10, there is only a weak magnetic anomaly in Trench 2's hearth.…”
Section: Results Of the 2012 Geophysical Surveymentioning
confidence: 99%
“…Moreover, the GIS environment facilitates other common research endeavors in geophysical archaeology. For example, map algebra methods or principal components analysis, common within GIS, may be utilized to integrate geophysical data from multiple survey modalities, permitting "fusion" of their information for greater subsurface insights (e.g., Nowaczinski et al 2015). Coupled with the insights it offers in student training, these advantages further underscore the importance of GIS to geophysical endeavors in archaeology.…”
Section: Discussionmentioning
confidence: 99%
“…They are therefore ideal for application to geophysical data, all of which are spatial in character, our focus here. They have been routinely employed for organizing and visualizing geophysical data and merging results with other information (Neubauer 2004;Gallo et al 2009;Nowaczinski et al 2015). Many GIS offer a highly varied suite of complex spatial data handling and processing tools that permit a wide variety of manipulations.…”
mentioning
confidence: 99%